Analysis of Interactive Communication, Incentive Program and User Experience on Bank Customer Decision Through Brand Image as Intervening Variable (Study on BNI Mobile Banking Users) - Zulfikar Aditya Rachman; Amie Kusumawardhani (Green Publisher Indonesia, 2025)
The background of this research stems from the rapid digital transformation in banking, which has not been fully matched by financial literacy and public understanding of digital services, as well as research gaps in previous findings on the influence of digital marketing variables on brand image and customer decisions. This study aims to analyze the influence of Interactive Communication, Incentive Program, and User Experience on bank customer decisions, with brand image as an intervening variable, among customers using Bank BNI digital banking services in Semarang City. The research addresses the gap between rapid digital transformation in banking and limited financial literacy, as well as inconsistencies in previous research findings. This study employs a quantitative approach with proportionate random sampling and Partial Least Squares (PLS) analysis. The results show that interactive communication and user experience have positive and significant effects on brand image, while the incentive program has a positive but insignificant effect. Brand image has a positive and significant influence on bank customer decisions, positioning it as an important link between digital marketing strategies and customer decisions. These findings confirm that strengthening interactive communication and superior user experience is more critical for brand image formation than merely providing financial incentives, offering strategic implications for banking management in designing competitive digital marketing strategies.